The Influence of Digital Payment, Social Media, E-Commerce, and Financial Literacy Use on The Consumer Behavior of Gen Z in Pondok Suguh District - Elnita Septiani; Wagini Wagini; Aji Sudarsono (LPPJPHKI Universitas Dehasen Bengkulu, 2026)
The advancement of digital technology has changed the pattern of transactions and interactions in society, especially among Generation Z who are familiar with the internet, social media, and e-commerce. This study aims to analyze the influence of digital payment, social media, e-commerce, and financial literacy on the consumer behavior of Generation Z in Pondok Suguh District. The study used a quantitative approach with an associative method on 97 respondents selected through a simple random sampling technique. Data were collected through a Likert scale questionnaire and processed using SPSS version 22. The results showed that social media had a significant effect on consumer behavior, while digital payment, e-commerce, and financial literacy had no partial effect. However, the four variables simultaneously had a significant effect with a coefficient of determination of 0.601. Thus, social media is a dominant factor influencing the consumer behavior of Generation Z. It is hoped that the younger generation will improve their financial literacy to be wiser in using digital technology.